Penerapan Shalat Dhuha dalam Pembentukan Karakter Siswa di MI Takhassus Ma’arif NU Prapagkidul Kabupaten Purworejo - Niya Uswatun Nuha; Imam Subarkah; Nurhidayah Nurhidayah (IAINU Kebumen, 2022)
This study aims to describe (1) the application of the Duha prayer at MI Takhassus Ma'arif NUPrapagkidul Purworejo Regency, (2) the supporting and inhibiting factors for the implementationof the Duha prayer, and (3) the impact of implementing the Duha prayer in building the characterof students at MI Takhassus Ma' arif NU Prapagkidul, Purworejo Regency. This research is aqualitative research with the type of phenomenological research. Collecting data in this study isby way of interviews, observation, and documentation. The research instrument used observationsheets and interviews. Data were analyzed using data reduction, data display, and drawingconclusions. Test the validity of the data using technique, source and time triangulation. Based onthe results of the study it can be concluded that: (1) The implementation of Duha prayer at MITakhassus Ma'arif NU Prapagkidul has been carried out in accordance with the predeterminedprogram: a) Planning: There is a schedule for holding Duha prayer, b) Implementation: Duhaprayer is held every morning ( 07:15 WIB), in the prayer room, in congregation, as many as twocycles, c) Monitoring: Dhuha prayer is coordinated, and accompanied by the homeroom teacher,there is a prayer monitoring book, d) Evaluation: there is punishment; (2) Supporting factors: a)Teacher commitment, b) Parental support, c) Sarpras, d) Sanctions. Inhibiting factors: a) Familybackground, b) Lack of discipline, c) Still crowded. (3) Impact of implementation: a) Discipline,b) Responsibility, and c) Care. As a reflection of the dhuha prayer program in character building.Overall, the implementation of the Duha prayer was good